Vietnam : Science, Technology, and Innovation Report 2020 Policy Brief - World Bank (World Bank, Washington, DC, 2021)
The science, technology, and innovation (STI) report provide analytical support for Vietnam’s upcoming ten-year STI strategy 2021-2030 and the socio-economic development strategy (SEDS) 2021-2030. The STI report and the accompanying policy brief have been prepared in response to a request from the Ministry of Science and Technology (MOST). The policy brief summarizes the key findings, recommendations, and lays out a STI roadmap to guide priority actions towards supporting business innovation in Vietnam. As the Coronavirus disease 2019 (COVID-19) triggered economic shock continues to spread globally and its impact deepens in Vietnam, the importance of technology adoption and innovation for business resilience as well as for productive growth has been amplified.